Nothing less than the Whole: Mario Mieli and the impossible harmony (Balthazar, 2022)
Following Mario Mieli’s close critical confrontation with Freudian theory, and his ambivalent relationship with it, this paper aims to inquiry the not only theoretical-practical horizon but, in the opinion of the writer, more properly “mystical” horizon in which Mieli’s intellectual and human experience, as well as the militant one, should be inscribed.  An experience and a militancy openly and faithfully revolutionary - with Freud and Marx as teachers to criticize and, ultimately, to overcome - that can be understood only if intertwined with the “mystical-foolish” tension which moved the author of Towards a Gay Communism: Elements of a Homosexual Critique.
Keywords: Mario Mieli; Sigmund Freud; Schreber; transexuality; gay communism; nascissism; mysticism